2019
DOI: 10.1002/humu.23925
|View full text |Cite
|
Sign up to set email alerts
|

Curating the gnomAD database: Report of novel variants in the globin‐coding genes and bioinformatics analysis

Abstract: Massive parallel sequencing technologies are facilitating the faster identification of sequence variants with the consequent capability of untangling the molecular bases of many human genetic syndromes. However, it is not always easy to understand the impact of novel variants, especially for missense changes, which can lead to a spectrum of phenotypes. This study presents a custom‐designed multistep methodology to evaluate the impact of novel variants aggregated in the genome aggregation database for the HBB, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Hypergeometric tests revealed that COAS, CORS and MIXED genes, but not TFs, were significantly protected (p < 0.01) from loss of function structural variation in normal tissues (GNOMAD 59 ) and significantly enriched in Pan-Cancer fitness genes 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Hypergeometric tests revealed that COAS, CORS and MIXED genes, but not TFs, were significantly protected (p < 0.01) from loss of function structural variation in normal tissues (GNOMAD 59 ) and significantly enriched in Pan-Cancer fitness genes 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, we launched Mutect2 in ‘tumor-only’ mode. We supplied Mutect2 with gnomAD 2.1.1 23 population frequency data. Next, we tried to eliminate FFPE artifacts using the LearnReadOrientationModel, GetPileupSummaries, and CalculateContamination tools according to the GATK best practice workflow for somatic short variant discovery.…”
Section: Methodsmentioning
confidence: 99%
“…Stage 1: For further analysis, we filtered out somatic variants with a population frequency threshold >0.5%, according to gnomAD 2.1.1. 23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromosomal location and type of the identified variants were retrieved in UCSC Genome Browser ( Navarro Gonzalez et al, 2021 ) and NCBI dbSNP ( Bhagwat, 2010 ). The MAFs of the variants were screened in several public databases with a large number of human samples, such as 1000 Genome Project ( n = 2504) ( Siva, 2008 ), NHLBI Exome Sequencing Project (GO-ESP) ( n = 6503) ( Amendola et al, 2015 ), The Exome Aggregation Consortium (ExAC) ( n = 60,706) ( Lek et al, 2016 ), gnomAD ( n = 15,708) ( Scheps et al, 2020 ), and NHLBI Trans-Omics for Precision Medicine (TOPMED) ( n = 60,000) ( Taliun et al, 2021 ). The function prediction of these variants was carried out by online software, PolyPhen-2 ( Adzhubei et al, 2010 ), and PROVEAN ( Choi et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%